A new achievement in green degradation of aqueous organic pollutants under visible-light irradiation - Abdollahi, Yadollah; Sabbaghi, Samad; Abouzari-lotf, Ebrahim; Jahangirian, Hossein; Sairi, Nor Asrina (IWA Publishing, 2018)
The global attention has been focused on degradation of the environmental organic pollutants through green methods such as advanced oxidation processes (AOPs) under sunlight. However, AOPs have not yet been efficient in function of the photocatalyst that has been used. In this work, firstly, CaCu3Ti4O12 nanocomposite was simultaneously synthesized and decorated in different amounts of graphene oxide to enhance photodegradation of the organics. The result of the photocatalyst characterization showed that the sample with 8% graphene presented optimum photo-electrical properties such as low band gap energy and a great surface area. Secondly, the photocatalyst was applied for photodegradation of an organic model in a batch photoreactor. Thirdly, to scale up the process and optimize the efficiency, the photodegradation was modeled by multivariate semi-empirical methods. As the optimized condition showed, 45 mg/L of the methylorange has been removed at pH 5.8 by 0.96 g/L of the photocatalyst during 288 min of the light irradiation. Moreover, the photodegradation has been scaled up for industrial applications by determining the importance of the input effective variables according to the following organics order>photocatalyst>pH> irradiation time.